A nemkonvencionális monetáris politika transzmissziós mechanizmusa, valamint a mennyiségi lazítás egyes pénzpiaci és makrogazdasági hatásai - Csiki Máté (Móra Akadémia, 2019)
As a result of the financial turbulence and the economic downturn following the global financial crisis of 2008–2009, the traditional monetary policy instruments were unable to help achieve monetary policy goals. In response, many central banks have adopted different types of unconventional instruments. The transmission mechanism of unconventional monetary policy – as central bank decisions affect output and inflation – differs from the theoretical framework of conventional monetary policy. In my study, I present the unconventional instruments used by the central banks of developed countries – FED, ECB, BoE – in recent years, and their effects on the financial market and the real economy, using theoretical models and some empirical evidence. According to the main findings of the empirical studies, the unconventional policy of the central banks significantly reduced long-term yields, stabilized the financial market. In addition, asset purchase programs of leading central banks had a significant real economic impact.